PENGUJIAN METALLOGRAPHY MATERIAL AISI 430 SUDU KINCIR AIR DENGAN HEAT TREATMENT DAN TANPA HEAT TREATMENT - Christofel Jarot Yudaputranto (Jurnal Ilmiah Teknik, 2023)
Metallography testing aims to be able to observe the microstructure. The steps that must be passed are preparing the test sample by cutting the specimen, mounting, sanding, polishing and etching. In material specimens without heat treatment, the results of the microstructure of ferrite and pearlite were obtained, with the conclusion that Ferrite is ferromagnetic up to temperature and is ductile, Pearlite is the result of a eutectoid reaction. The faster the cooling rate, the finer the grain and the better the mechanical properties of the steel. Explanation of the phases of material specimens with heat treatment. The difference from specimens without heat treatment is the formation of a bainite phase. This bainite phase was formed due to heat treatment which was carried out for 1 hour at 550â°C. The quenching process using oil greatly influences the results of the formation of the bainite phase, because oil has better heat absorption properties. The conclusion of this paper is the difference in the microstructure of material specimens without heat treatment and specimens with heat treatment. In the specimen without heat treatment, two ferrite phases and a pearlite phase were obtained. while the heattreated specimens yielded three ferrite, pearlite and bainite phases. This bainite phase was formed due to heat treatment with a temperature of 550â°C for 1 hour.